Work Stress Among Nurses in a Private Hospital in Lumajang Indonesia - Dewanto, A (KnE Life Sciences, 2018)
The issue of nurses’ turnover is rising worldwide as it causes instability of nursing workforce. In fact, a hospital needs a sustainable and highly committed nursing workforce to provide high-quality patient care. Work stress is a crucial factor influencing nurses’ performance, organizational commitment, and one of the key turnover predictors. Thus, knowing the current level of nurses’ work stress and its influencing factors will be imperative. This study aims to determine the level of work stress of nursing personnel in a private hospital in Lumajang Indonesia and identify factors that influence the stress. This study used a cross-sectional research design. A questionnaire was used to collect data from 40 nurses in a private hospital in Lumajang Indonesia. Respondents were asked to rate their perception of work stress and aspects of working conditions using a five-point Likert scale. All items in the instrument have passed the validity and reliability test. Data were analyzed using descriptive statistics and multiple linear regression. The results of this study show that around two-fifth of the nurses experience moderate to high level of work stress. Of the research variables, pay, management, and health and safety were found to have a significant influence statistically on the work stress. Among those three variables, hospital health and safety variable are considered as the most dominant factor. The findings are in line with previous research about factors influencing work stress, but in addition, this study identifies hospital health and safety as the most dominant factor. This result could be useful for the hospital manager in prioritizing improvement on the problematic aspects of nurses’ working condition to reduce nurses’ work stress. Keywords: work stress, nurse, working conditions